2007
DOI: 10.1021/jp067776s
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics of 0.5 cm Vertically Aligned Single-Walled Carbon Nanotubes

Abstract: Half-centimeter-high mats of vertically aligned single-walled carbon nanotubes were grown at 600 degrees C by point-arc microwave plasma chemical vapor deposition. The mats were produced from 0.5 nm of an Fe catalyst layer, thus showing one of the highest catalytic yields of approximately 105 times. The growth process shows a lack of poisoning of the catalyst, in contrast to other reports. The experimental results confirm that the growth rate is ultimately limited by the gas phase diffusion of hydrocarbon radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
158
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(162 citation statements)
references
References 30 publications
(68 reference statements)
4
158
0
Order By: Relevance
“…Tortuosity τ in our estimation was approximated to 1.5 in all cases, because it is the typical value for aligned MWNTs (ref 26). As discussed in the main text, error here will not significantly affect in the overall conclusions, i.e.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Tortuosity τ in our estimation was approximated to 1.5 in all cases, because it is the typical value for aligned MWNTs (ref 26). As discussed in the main text, error here will not significantly affect in the overall conclusions, i.e.…”
mentioning
confidence: 89%
“…However, the influences of these parameters are very limited because to bring diffusion limited processes to the reaction controlled region one usually needs to decrease φ by two orders of magnitude, as expressed in Equation (7). One promising approach is to pattern the continuous CNT film into pillar-like or sheet-like micron structure to allow easy side diffusion, as demonstrated by Zhong et al 26 However, we found this strategy didn't work for our F-MWNT in yielding longer CNT arrays. 30 This means there exists strong diffusion resistance in P-SWNT but not in F-MWNT, which agrees well with the above calculated results on these two situations.…”
mentioning
confidence: 99%
“…Water also reacts with the wall of nanotubes even though the wall is more impervious to oxidation than carbonaceous impurities. 11 Plasma generally activates carbon source molecules so that not only the nanotube growth but also the deposition of carbonaceous impurities occurs at lower temperature in plasma CVD than in thermal CVD. Therefore, the larger amount of water in our plasma CVD is necessary to enhance and preserve catalyst activity by removing larger amount of carbonaceous impurities on the catalyst surface.…”
Section: Resultsmentioning
confidence: 99%
“…9) Over the last few years, there have been many reports on the synthesis of VACNTAs using CVD-based methods. Many of these techniques, however, have stronger requirements on the equipment, 10), 11) limiting CNT production to only the laboratory range. More have focused on preparing ideal catalysts on the surface of substrates because it is generally believed that catalysts play a critical role in the synthesis of CNTs.…”
Section: Introductionmentioning
confidence: 99%